CATALYSTS AND INHIBITORS OF POLITICAL CAREER IN RUSSIA - I. A. Lavrov (Вестник университета)
Studying the basic principles of the political elite formation in Russia is the cornerstone for understanding the country’s future strategy and its development vector, since the development strategy will depend on those people who will be at the helm of the country’s governance. There is already a dynamic process of rejuvenating the authorities, representatives of Generation X are actively striding along the political career ladder and gain high positions. The analysis of the career background of “young” politicians, the main political career elevators, its catalysts and inhibitors, and the speed of professional formation has been reflected in our research. The research was carried out on the base of biographies of 370 civil servants who, as of March 1, 2019, held the posts of deputy ministers or deputy heads of federal departments. Biographies were taken from open sources and were digitized in a database. The study examined the career paths of politicians, on the base of which it is possible to allocate the key institutions of the political elite formation and political career elevators.